Production and operations management study on Domatita L and Sons Food Products - Diaz, Irma R.; Fulgencio, Charisma B.; Jumaquio, Jayson S. (Diliman, Quezon City College of Engineering, 2000)
In the analysis of the Production System and Management of Manufacturing Operations, the group cited Dometita L and Sons Food Products as the domain of the whole study. In dealing with this company, a systematic procedure is implemented beginning with the product and process documentation. Existing problems are synthesized and analyzed through Methods Engineering Tools and P/OM strategies in Aggregate Production Planning, Inventory Management, and Scheduling. Through these techniques the group was able to identify sound recommendations for the company such that the company will realize improvements and productivity gains.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Domatita L and Sons Food Corporation; Food industry; Production engineering